Glutathione‐S‐transferase T1 genotyping and phenotyping in psoriasis patients receiving treatment with oral fumaric acid esters. (12th March 2013) - Gambichler, T.; Kreuter, A.; Susok, L.; Skrygan, M.; Rotterdam, S.; Höxtermann, S.; Müller, M.; Tigges, C.; Altmeyer, P.; Lahner, N.
Abstract Background Glutathione S‐transferases (GSTs) are involved in detoxification of xenobiotics such as fumaric acid esters (FAE). Objectives To perform GSTT1 geno‐ and phenotyping in psoriasis patients treated with FAE to find out whether the responder status and/or occurrence of side‐effects are associated with allelic variants and enzymatic activity of GSTT1. Methods We treated 106 psoriasis patients with FAE. GSTT1 genotyping was performed using PCR, phenotyping was carried out by means of a validated high performance liquid chromatography assay at baseline and under treatment. Results The distribution of GSTT1 genotypes was as follows: 31% *A/*A; 49% *A/*0; 20% *0/*0. GSTT1 phenotypes as expressed in enzyme activity significantly differed between conjugators classes. (P < 0.001). GSTT1 activity under treatment was significantly (P = 0.0001) increased when compared with baseline. There were no significant associations between the aforementioned GSTT1 pheno‐ and genotypes and clinical parameters such as psoriasis area and severity index (PASI)50, adverse effects and FAE dosage (P > 0.05), except for the frequent occurrence of reduction (>50%) of circulating lymphocytes in patients with *0/*0 GSTT1 status (P = 0.036; odds ratio: 6, 95% CI: 1.1–32). Conclusion GSTT1 geno‐ and phenotypes significantly correlate in psoriasis patients and do not substantially differ from healthy controls. Response to FAE does likely not depend on GSTT1. However, *0/*0 GSTT1 status is a predictor for the occurrence of marked reduction of lymphocyte counts under FAE therapy. Notably, FAE seem to enhance GSTT1 enzyme activity in high and low conjugators.